Measurement of concrete consistency through an automated slump test device: their validation and potentialities - Pereira, João Batista [UNESP]; Maciel, Geraldo de Freitas [UNESP] (FapUNIFESP (SciELO), 2021)
From the development of a mechanical device capable of performing the slump test of concrete, this work evaluated the equipment's ability to simulate the test recommended by norm. Slumps using the standard test and the equipment developed were measured for different compositions of conventional concrete. The results confirmed the equipment's capacity to perform the slump test both in the lifting the Abrams cone and the slump reading, besides to allowing for less experimental errors associated with the operator during the test. Yield stress and plastic viscosity properties of the concretes produced were also evaluated-for this, empiri-cal models based on rheometric measures were used (modified slump test via BTREOM rheometer) verifying results compatible with those reported in the literature. It should be emphasizes to need for a precise measurement of the slump, in order not to compromise the rheological evaluations of the material, given the high dependence (sensibility) of yield stress and even more of the plastic viscosity to that measure. Furthermore, the slump test equipment allowed for a more complete flow characterization during the test, providing the descent temporal behavior of the material (as an indirect measure of the viscosity) until final slump.
Medida de consistência do concreto pelo abatimento do tronco de cone automatizado: sua validação e potencialidades
Keywords: Concrete; Plastic viscosity; Rheology; Slump test; Yield stress